This changes everything : capitalism vs. the climate - Klein, Naomi, 1970- (Simon & Schuster, 2014)
"Klein argues that climate change isn't just another issue to be neatly filed between taxes and health care. It's an alarm that calls us to fix an economic system that is already failing us in many ways. Klein ... builds the case for how massively reducing our greenhouse emissions is our best chance to simultaneously reduce gaping inequalities, re-imagine our broken democracies, and rebuild our gutted local economies"--